A commercially available SRP vaccine reduces prevalence of E. coli O157:H7 in feces of beef cattle under commercial feedlot conditions - Butler, B.A.; Loneragan, G.H.; Thomson, Daniel U.; Nagaraja, Tiruvoor G.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Of all food safety challenges facing the beef industry, Escherichia coli O157:H7 has consistently presented the greatest economic remonstrance to meat packers and retailers. Cattle naturally shed E. coli O157:H7 in their feces, and it is a source of carcass contamination at harvest. If contaminated trim enters the food supply and is subsequently prepared incorrectly, it can lead to the human condition known as hemorrhagic colitis. In children or elderly people, an E. coli O157:H7 infection may lead to a more serious form known as hemolytic uremic syndrome, which is potentially lethal. Although the majority of previous research has been dedicated to reduction in contamination post-harvest, recent focus has shifted to pre-harvest mitigation of E. coli O157:H7. Post-harvest procedures are effective, so there is less room for improvement than in pre-harvest mitigation. Also, reducing the E. coli O157 burden entering the plant may improve the efficacy of post-harvest tools and ultimately reduce human illness. Most previous research efforts have been focused on controlling E. coli within the abbatoir. Over the last 10 years, the National Cattlemen’s Beef Association has estimated E. coli O157 to cost the industry $2.67 billion. The E. coli O157 siderophore-receptor and porin-based (SRP) vaccine has been shown to reduce fecal shedding of E. coli in cattle in laboratory conditions as well as field conditions. In 2007, the vaccine received conditional licensure from the USDA. The objective of this study was to determine the efficacy of the SRP vaccine by (1) quantifying the prevalence of E. coli O157:H7 in vaccinated cattle under field conditions and (2) monitoring anti-SRP antibody titer levels immediately prior to harvest.
Keywords: Beef; E. coli O157:H7; Commerical feedlot; SRP Vaccine